THEORY OF KARMA, CASTE SYSTEM AND CONCEPT OF REINCARNATION AND THEIR IMPACT ON INDIAN SOCIETY: AN ANTHROPO-PHILOSOPHICAL READING - Andrade, Joachim (2020)
This article intends to make an approximation to Indian society from three distinct concepts of Hindu tradition: Karma theory, reincarnation and caste system. These three pillars sustain the entire social system which includes family, society and religion, such a way that sometimes it seems that the individual is perpetually imprisoned in it without finding a way out. The article presents the mechanisms involved in the construction of these three pillars and also shows the appropriate paths elaborated by Hinduism. At the first moment we intend to map the Hindu tradition, which contemplates the construction of the Hindu Trinity and then presents the three pillars in a sequential way and finally winds up with the treatment of Hindu ethical principles of life that keep Hinduism alive even today.